Therapeutic effect of a cleft lip teat on infants with respiratory and feeding disorders: Two case reports. Issue 31 (August 2018) - Pawlukowska, Wioletta; Rychert, Monika; Urbanowicz, Ewa; Romanowska, Hanna; Rotter, Iwona; Giżewska, Maria
Abstract: Rationale: Existing research into the effects of teat application has mainly focused on its negative and positive influence on the development of the oral cavity. Our work demonstrates that apart from changing the setting of the articulatory organs, the teat can also affect the quality of breathing, eating and sleeping. Patients concerns: We described the cases of 2 children: a 19-month-old girl and a 2.5-month-old boy, who had breathing disorders due to withdrawal of the tongue and impaired food intake. Intervention: The babies were bottled fed with a special teat for cleft lip patients to observe the influence of the teat on the setting of the articulatory organs and breathing. Diagnosis: We suspected that the specific construction of the teat—the wide outer part and the short internal part—would affect children's reflexes and articulatory organs so as to force the frontal position of the tongue, which was meant to facilitate breathing and eating. Outcomes: It was found that feeding with the cleft lip teat stimulates the gyro-linguistic muscle, which results in the proper position of the tongue and consequently better breathing and improved quality of sleep. Lessons: A specialist bottle teat designed for babies with cleft lips can constitute an effective tool in the therapy of nonspecific respiratory disorders resulting from improper position of the tongue and other articulatory organs.